2009
DOI: 10.4250/jcu.2009.17.3.96
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Right Atrial Aneurysm Incidentally Found in Old Age

Abstract: Right atrial aneurysm is a rare abnormality of unknown origin. Approximately half of patients with right atrial aneurysm show no symptoms. Right atrial aneurysm is usually detected by chance at any time between fetal and adult life and can be associated with atrial arrhythmia and systemic embolism. The diagnosis of right atrial aneurysm can be established with echocardiography, computed tomography (CT) or magnetic resonance imaging (MRI). Because of thromboembolic risk, aneurysmectomy is usually recommended. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 5 publications
0
10
0
3
Order By: Relevance
“…(Fig. 13 Both the modalities are useful in confirming the connection of the aneurysm to the RAA and studying its relation to other structures like descending thoracic aorta. 12 In patients with difficult TTE images and or unclear diagnosis, TEE with contrast study and has been reported to increase sensitivity for diagnosing RAAA, however, the sensitivity was still low at 33%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Fig. 13 Both the modalities are useful in confirming the connection of the aneurysm to the RAA and studying its relation to other structures like descending thoracic aorta. 12 In patients with difficult TTE images and or unclear diagnosis, TEE with contrast study and has been reported to increase sensitivity for diagnosing RAAA, however, the sensitivity was still low at 33%.…”
Section: Resultsmentioning
confidence: 99%
“…CT angiography and MRI are excellent adjuvant imaging tools, in patients in whom the diagnosis is not clear on TEE, with high sensitivity and specificity. 13 Both the modalities are useful in confirming the connection of the aneurysm to the RAA and studying its relation to other structures like descending thoracic aorta. 2 A 24-hour Holter recording should be requested in patients complaining of palpitations and/or normal ECG for the evaluation of atrial tachyarrhythmias.…”
Section: Discussion: Epidemiology Pathogenesis Gross and Microscopmentioning
confidence: 99%
“…Telecardiography and echocardiography were used for diagnosis of atrial enlargement and cardiac functions. Echocardiography can show underlying pathologies in addition to right atrial dilatation and can guide our treatment, but CT or cardiac magnetic resonance imaging (MRI) is more sensitive and specific by helping to describe cardiac structure and function (4) . Although right atrial aneurysm resection was firstly performed by Marrow and Behrendt in 1968, it is still controversial to perform this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in patients who are younger, symptomatic, or who have evidence of thrombosis, surgical excision appears to be the preferred therapy [ 2 , 5 , 12 15 ]; a Cox-maze procedure may also be performed to treat concomitant arrhythmias [ 10 , 14 ]. The rarity of RAA aneurysms makes it difficult to determine whether such an intervention confers a survival benefit, however [ 20 ].…”
Section: Discussionmentioning
confidence: 99%